Four new species of genus Parallaxis McAtee (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini) from Argentina, with a key to known species - Catalano, María Inés; Paradell, Susana L.; Dietrich, Christopher H. (Zootaxa, 2013)
Four new species of Parallaxis McAtee are described from Argentina, P. jujuiensis sp. n., P. misionensis sp. n., P. tucumanensis sp. n. and P. virlai sp. n. Detailed morphological descriptions and illustrations of the new species and a key to males of known species are provided.